2017
DOI: 10.1111/1753-6405.12595
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent inhalant abuse leads to other drug use and impaired growth; implications for diagnosis

Abstract: Adolescent inhalant abuse increases the risk for subsequent and earlier drug use. It also impairs growth such that individuals meet 'failure to thrive' criteria, representing an improved diagnostic model for inhalant abuse. Implications for Public Health: Improved diagnosis of adolescent inhalant abuse may lead to earlier detection and enhanced health outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 33 publications
1
13
0
2
Order By: Relevance
“…Indeed, one of the most profound, but underexplored, consequences of inhalant abuse is its effect on energy balance. In humans, adolescent inhalant abuse is associated with weight loss, and emaciation; findings which are supported by meta‐analysis . This meta‐analysis found a significant dose‐response relationship to toluene‐induced weight impairments, with the lowest concentration band (0‐500 ppm) having no significant impact on body weight, suggesting that occupational level exposure does not impact body weight in the same way as inhalant abuse .…”
Section: The Effects Of Inhalant Abuse On Energy Balancementioning
confidence: 58%
See 2 more Smart Citations
“…Indeed, one of the most profound, but underexplored, consequences of inhalant abuse is its effect on energy balance. In humans, adolescent inhalant abuse is associated with weight loss, and emaciation; findings which are supported by meta‐analysis . This meta‐analysis found a significant dose‐response relationship to toluene‐induced weight impairments, with the lowest concentration band (0‐500 ppm) having no significant impact on body weight, suggesting that occupational level exposure does not impact body weight in the same way as inhalant abuse .…”
Section: The Effects Of Inhalant Abuse On Energy Balancementioning
confidence: 58%
“…This meta‐analysis found a significant dose‐response relationship to toluene‐induced weight impairments, with the lowest concentration band (0‐500 ppm) having no significant impact on body weight, suggesting that occupational level exposure does not impact body weight in the same way as inhalant abuse . Furthermore, one cohort study found that the weight suppressing effects of inhalant abuse was not mediated by other substance use, suggesting that inhalants are a strong mediator of this effect even with other drug‐drug interactions . Indeed, this effect on body weight is listed as a warning sign of inhalant abuse .…”
Section: The Effects Of Inhalant Abuse On Energy Balancementioning
confidence: 92%
See 1 more Smart Citation
“…Inhalant abuse is predominantly associated with early adolescence [3, 4], thus the peak period of exposure to toluene overlaps with the adolescent growth spurt, characterised by a rapid increase in body weight and height at around 12–15 years of age in males [5]. In humans, inhalant abuse has been associated with emaciation [6], weight impairment [7], and reduced height trajectory persisting into sustained abstinence [7, 8]. However, the mechanisms underlying these growth impairments remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Suicidal thoughts and behaviour may also emerge from age 11 (from a longitudinal study of American sixth-grade students) [ 13 ] or even younger [ 14 , 15 ], though there is a lack of consensus regarding whether suicidal motives can be attributed to children younger than 12 [ 15 , 16 , 17 ]. In relation to alcohol and other drug use, there are drug types more prone to experimentation by young adolescents, including inhalants [ 7 , 18 ] and analgesics [ 7 ]. Both substances have relatively high rates of use in Australian 12-year olds that participated in the Australian Secondary Schools Alcohol and Drugs Survey [ 7 ], which would suggest that experimentation has begun at an earlier age, though this is not identified by population level surveys.…”
Section: Introductionmentioning
confidence: 99%